Time savings of weekly versus three-times-per-week administration of erythropoiesis stimulating agents in United States dialysis patients. (1st February 2016) - Stephens, J. Mark; Emerson, Larry C.; Spry, Leslie A.; Caloyeras, John P.; Anderson, Ernest R.; Reitan, John F.; Ashfaq, Akhtar
Abstract: Objective: Previous research suggests that erythropoiesis stimulating agent (ESA) administration in dialysis is a time-consuming task and switching to less frequently dosed ESAs may offer operational efficiencies. Our objective was to describe and measure the time spent on tasks in the ESA administration process in US dialysis centers, and to estimate potential efficiency gains of using weekly (QW) administration vs three-times-per-week (TIW) administration. Methods: We conducted a time and motion study of staff time required to prepare, administer and document ESA doses. Dialysis centers using intravenous administration of TIW epoetin alfa (EPO) or QW darbepoetin alfa (DPO) were selected in pairs (one EPO, one DPO) from the same organization to help control for differences in ESA protocols and staffing patterns across organizations. ESA-related tasks were timed by trained observers. Time savings of TIW vs QW administration were estimated. Staff were interviewed about alternate activities that could be accomplished if time were saved in the ESA process. Results: A total of 200 administrations were observed (81 DPO, 119 EPO). A mean of 2.26 (95% CI: 2.1–2.5) minutes per dose were required for ESA administration. ESA process time per administration did not vary significantly between EPO and DPO ( p  = 0.83). Estimated potential monthly staff time savings for an average facility of 70 patients totaled 23 hours, due to fewer ESA administrations using QW DPO. Patient education and fulfillment of care plans were identified as opportunities for improved care processes that could be implemented if staff time was freed up from the ESA process. Limitations: Results should not be generalized to other countries, ESAs and/or dosing frequencies. Conclusions: Switching from TIW EPO to QW DPO can result in time savings due to fewer administrations and provide opportunities to redirect nurse time towards activities aimed at improving patient care.